Association Between the Polymorphism of Angiotensin-Converting Enzyme Gene and Interleukin-1 Beta Gene and the Response to Erythropoietin Therapy in Dialysis Patients with Anemia - Dzekova Vidimliski, Pavlina; Eftimovska-Otovikj, Natasha; Nikolov, Igor; Selim, Gjulshen; Rambabova Bushljetic, Irena; Pushevski, Vladimir; Karanfilovski, Vlatko; Matevska-Geshovska, Nadica; Dimovski, Aleksandar (Walter de Gruyter GmbH, 2023)
The polymorphism of the angiotensin-converting enzyme (ACE) gene and interleukin-1 beta (IL-1b) gene could be associated with resistance in the treatment of anemia in dialysis patients with recombinant human erythropoietin (rHuEPO). The aim of the study was to evaluate the association between the polymorphism of the ACE and IL-1b genes and the response to rHuEPO therapy in dialysis patients with anemia.
Keywords: anemia; dialysis; erythropoietin; gene; polymorphism; therapy